Development of egg yolk-free mayonnaise using rice protein with xanthan gum - Baek, Manhee; Jeon, Sujin; Jeong, Semin; Mun, Saehun (Food science and biotechnology, 2025)
In this study, egg yolk-free mayonnaise was produced by replacing egg yolk with rice protein (RP) and the preparation conditions were standardized to obtain rheological properties similar to those of commercial mayonnaise. Specifically, RP was isolated at pH 2 to address its insolubility issues in acidic conditions, aiming to enable direct application in acidic foods such as mayonnaise. All mayonnaise samples showed shear thinning properties, and the yield stress increased with the increase in RP and xanthan gum (XG) content, compared to mayonnaise containing egg yolk. Moreover, comparing the viscoelasticity of commercial mayonnaise with that of mayonnaise containing 0.1 or 0.2 wt% XG revealed an increase in storage modulus and loss modulus with the rise in RP and XG content. These results confirmed that RP isolated at pH 2 could be used to prepare mayonnaise as a natural emulsifier to replace egg yolk.